Spectral Mapping Theorem for the Davies-Helffer-Sjöstrand Functional Calculus - Claire, N.S. (Журнал математической физики, анализа, геометрии, 2012)
We give a direct non-abstract proof of the spectral mapping theorem for the Davies–Helffer–Sjöstrand functional calculus for linear operators on Banach spaces with real spectra and consequently give a new non-abstract direct proof for the spectral mapping theorem for self-adjoint operators on Hilbert spaces. Our exposition is closer in spirit to the proof by explicit construction of the existence of the Functional Calculus given by Davies. We apply an extension theorem of Seeley to derive a functional calculus for semi-bounded operators. Представлено прямое неабстрактное доказательство теоремы об отображении спектра для функционального исчисления Девиса-Хельффера-Сьостранда для линейных операторов в банаховых пространствах с реальными спектрами, а следовательно, дано новое неабстрактное прямое доказательство теоремы об отображении спектра для самосопряженных операторов в гильбертовых пространствах. Наше представление по духу ближе к доказательству благодаря явной конструкции существования функционального исчисления, данной Дэвисом. Мы применяем теорему расширения Сили, чтобы получить функциональное исчисление для полуограниченных операторов.